Stable impact and contact force control by UAV for inspection of floor slab of bridge. (2nd October 2018) - Ikeda, Takahiro; Yasui, Shogo; Minamiyama, Satoshi; Ohara, Kenichi; Ashizawa, Satoshi; Ichikawa, Akihiko; Okino, Akihisa; Oomichi, Takeo; Fukuda, Toshio
ABSTRACT: This paper describes the contact force control on an unmanned aerial vehicle (UAV) developed to inspect the floor slabs of bridges. Our UAV is equipped with a three degree-of-freedom manipulator on top of the UAV body. To control the UAV for stable contact with the slab surface, the impact force should be considered. The impact force is modeled based on Hertzian contact stress. The control strategy of the UAV is cascade control separated into attitude control and position-force control. The attitude, position and force feedback are PID control. The force feedback is integrated into the position feedback seamlessly, and the output of the force feedback is added to the desired end-point position of the manipulator. This paper focuses on contact of the UAV and the floor slab. Therefore, the UAV is modeled considering the impact force in the vertical direction. The control method in the vertical direction is described, and then the altitude control and the contact force control are assessed. The altitude of the UAV was controlled with a 0.45 [sec] delay during ascending and 1.76 [sec] during descending. The UAV could control the contact force with mean error 1.61 ± 1.08 [N] while the desired contact force was 3 [N]. GRAPHICAL ABSTRACT: